1978
DOI: 10.1017/s0033822200003969
|View full text |Cite
|
Sign up to set email alerts
|

US Geological Survey Radiocarbon Dates XIII

Abstract: This list contains the results of some measurements made between 1965 and 1973. Samples are counted in the form of acetylene gas, as previously, and ages computed on the basis of the Libby half-life, 5568 ± 30 years. The dates have not been corrected for fractionation by a δ13C measurement. The error listed, always larger than the one-sigma statistical counting error commonly used, takes into account possible fractionation in the laboratory and in nature and the variability experienced with replicate samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Throughout the Holocene, thermokarst processes have continued to operate, gradually lowering the original land surface. Thermokarst lake formation during that time falls within the range of other published thermokarst lake basal dates for the Seward Peninsula (Spiker et al, 1978;Kaufman and Hopkins, 1985) and the circum-arctic (Walter et al, 2007;Reyes and Cooke, 2011). The age of the lowermost dated sample in unit D of 8370 AE 50 yr BP falls in the period of a pronounced early Holocene climate warming in NW North America (McCulloch and Hopkins, 1966;Detterman, 1970;Ritchie et al, 1983;, a time when thermokarst lake formation peaked in Alaska and other high latitude regions (Walter et al, 2007) and intense peatland formation occurred in Alaska (Jones and Yu, 2010).…”
Section: Tablesupporting
confidence: 71%
“…Throughout the Holocene, thermokarst processes have continued to operate, gradually lowering the original land surface. Thermokarst lake formation during that time falls within the range of other published thermokarst lake basal dates for the Seward Peninsula (Spiker et al, 1978;Kaufman and Hopkins, 1985) and the circum-arctic (Walter et al, 2007;Reyes and Cooke, 2011). The age of the lowermost dated sample in unit D of 8370 AE 50 yr BP falls in the period of a pronounced early Holocene climate warming in NW North America (McCulloch and Hopkins, 1966;Detterman, 1970;Ritchie et al, 1983;, a time when thermokarst lake formation peaked in Alaska and other high latitude regions (Walter et al, 2007) and intense peatland formation occurred in Alaska (Jones and Yu, 2010).…”
Section: Tablesupporting
confidence: 71%
“…6a). One date from Spiker et al (1978;W-2806) is reported in Hopkins (1988) as overlying the tephra. This date provides an additional constraint on the model although it is unclear how it relates to the tephra stratigraphically.…”
Section: Devil Mountain Lakes Maar Tephramentioning
confidence: 99%
“…al., 1961I Liu and Colermn, 1981ISGS Tamers, 1966IVIC Tauber, 1973K Tauber, 1968K Tauber, 1964K Tauber, 1962K Tauber, 1960K Olson and Broecker, 1961L Olson and Broecker, 1959L Hubbs and Bien, 1967LJ Hubbs, et. al., 1965LJ Crane and Griffin, 1972M Crane and Griffin, 1968M Crane and Griffin, 1964M Crane and Griffin, 1961M Spiker, et. al., 1978W Spiker, et.…”
Section: Appendix II Citaticns -Scien3ementioning
confidence: 99%
“…al., 1964Sainsbury, et. al., 1965Schweger, 1982Schweger, 1976Sellmann and Brown, 1973Spiker, et. al., 1978 Stuckenrath and Mielke, 1972Stuiver and Deevey, 1961Stuiver, et.…”
mentioning
confidence: 99%
See 1 more Smart Citation